MADRASAH DINIYAH TAKMILIYAH DI KOTA BANDUNG: MENUJU PENCAPAIAN STANDAR PELAYANAN MINIMUM: MADRASAH DINIYAH TAKMILIYAH IN BANDUNG: TOWARD MINIMUM SERVICE STANDARDS ACHIEVEMENT - Mulyana Mulyana (Balai Penelitian dan Pengembangan Agama Jakarta, 2015)
This article presents the results of an evaluation study of non-formal Islamic education, Madrasah Diniyah Takmiliyah (MDT) in Bandung, West Java. The evaluation study was conducted to assess whether MDT has met the Minimum Service Standards (MSS) as they are stipulated in the decree of Director General of Islamic Education of Ministry of Religious Affairs No. 6710/2014. Fieldwork was conducted on 16 February to 5 March 2015 in two sub-districts in Bandung, the sub-district of Bandung Kulon, where observations were performed on 4 Madrasah Diniyah Takmiliyah, and the sub-district Antapani, where observations were made in 3 Madrasah Diniyah Takmiliyah. This study uses multiple data collection techniques, including interview, observation and documentation study. This study found that Madrasahs Diniyah Takmiliyah have met most of Minimum Service Standards, including level of accessibility (it was measured through students’ mileage from their houses to madrasahs), the minimum level of teachers education (graduated from bachelor degree S1, diploma-IV or Islamic boarding schools), the number of students per class and teacher/students ratio. The components of Minimum Service Standards which have been met largely by Madrasah Diniyah Takmiliyah, namely the minimum education level of the head of MDT, the availability of separate rooms for teachers and heads of MDT, the availability of reference books and enrichment books, the availability of teaching aids and the absence of supervisor for MDT.Keywords: Madrasah Diniyah Takmiliyah, Minimum Service Standards, evaluation studies, religious education. Artikel ini menyajikan hasil penelitian evaluasi tentang Madrasah Diniyah Takmiliyah (MDT) di Kota Bandung, Jawa Barat. Penelitian evaluasi ini dilakukan untuk mengkaji apakah MDT telah memenuhi Standar Pelayanan Minimal (SPM) sebagaimana telah ditetapkan dalam SK Dirjen Pendidikan Islam Kementerian Agama No. 6710/2014. Penelitian lapangan dilakukan antara 16 Februari - 5 Maret 2015 di dua kecamatan di Kota Bandung, yaitu Kecamatan Bandung Kulon, di mana obsrvasi dilakukan di 4 MDT dan Kecamatan Antapani, di mana observasi dilakukan di 3 MDT. Teknik pengumpulan data mengkombinasikan wawancara mendalam, observasi, dan studi dokumentasi. Penelitian ini menemukan, bahwa MDT telah memenuhi sebagian komponen SPM. Komponen-komponen SPM yang telah dipenuhi oleh sebagian besar MDT meliputi tingkat aksesabilitas (yang diukur dengan jarak tempuh siswa dari rumah ke MDT), tingkat pendidikan minimal guru (lulusan S1, D-IV atau pesantren), jumlah siswa perkelas dan rasio guru-siswa. Adapun komponenkomponen SPM yang belum dapat dipenuhi sebagian besar MDT adalah tingkat pendidikan minimal kepala MDT, ketersediaan ruang terpisah bagi guru dan kepala MDT, ketersediaan buku referensi dan buku pengayaan, ketersediaan alat peraga, dan ketiadaan pengawas bagi MDT. Kata Kunci: Madrasah Diniyah Takmiliyah, Standar Pelayanan Minimal, penelitian evaluasi, pendidikan keagamaan.